DETERMINATION OF POOR GLYCEMIC CONTROL RATE AND RELATED FACTORS IN OUTPATIENTS WITH TYPE 2 DIABETES AT THU DUC GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the rate of poor glycemic control among outpatients with type 2 diabetes at Thu Duc General Hospital and to evaluate some related factors.Subjects and methods: A cross-sectional descriptive study was conducted on 355 patients with type 2 diabetes mellitus receiving outpatient treatment and follow-up between May and December 2024. The study sites included endocrinology, cardiology, family medicine, and internal medicine clinics. Patients with communication or cognitive impairments, as well as those with medical conditions affecting HbA1c test accuracy, were excluded from the study.Results: The mean age was 59.7 ± 11.96 years (range: 21-91), with the majority aged 51-70 years (63.9%). Females accounted for 56.2%. The mean duration of diabetes was 7.9 years. Overweight/obesity was observed in 34.7%, and central obesity in 70.4% (66% in females). Most patients were treated with oral hypoglycemic agents alone (83.1%), 14.9% received combined oral drugs and Insulin, and 2% used Insulin only. Overall, 16.9% of patients were on Insulin therapy. Regarding adherence, 12.4% adhered well, 37.2% poorly, and more than 50% moderately. Good adherence to dietary recommendations and physical activity was reported in 47.3% and 38.9%, respectively. Poor glycemic control (HbA1c ≥ 7%) was found in 57.5% of patients, with 56.1% failing to achieve fasting glucose targets. Chi-square analysis revealed a significant association between treatment adherence (medication, diet, exercise) and glycemic control (p = 0.001).Conclusion: Glycemic control among outpatients with type 2 diabetes at Thu Duc General Hospital was more favorable compared to some other domestic studies. Duration of diabetes, medication adherence, diet, and physical activity were strongly associated with glycemic outcomes.
Keywords: Poor glycemic control, type 2 diabetes, Thu Duc General Hospital.